John L. Campbell, J. Rogers Hollingsworth, Leon Lindberg, (eds.), Governance of the American Economy, Cambridge: Cambridge University Press, 1991, 462 s., £ 15.95 (pb.); J. Rogers Hollingsworth, Philippe C. Schmitter, Wolfgang Streeck, (eds.)3 Governing C - Chr. Sidenius, Niels (Politica, 1994)
John L. Campbell, J. Rogers Hollingsworth, Leon Lindberg, (eds.), Governance of the American Economy, Cambridge: Cambridge University Press, 1991, 462 s., £ 15.95 (pb.); J. Rogers Hollingsworth, Philippe C. Schmitter, Wolfgang Streeck, (eds.)3 Governing Capitalist Economies. Performance and Control of Economic Sectors, New York/Oxford: Oxford University Press, 1994, 316 s., $ 45.00 (hb.)